School Management to Magnify the Quality of Inclusive Early Childhood Education Through Sekolah Penggerak - Yetty Faridatul Ulfah; Annafi' Nurul 'Ilmi Azizah; M. Fatchurrohman; Nailla Faizzatis Syifa (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the school management practices of inclusive Early Childhood Education at Harapan Bunda Wita within the Sekolah Penggerak (Mover School) program. It focuses on the role of effective management in enhancing educational quality through curriculum integration and teacher competency development. Unlike previous research that typically centers on the roles of principals or teachers, this study explores broader management strategies aimed at improving educational outcomes. This research employed a qualitative descriptive design using a case study approach. The study was conducted at Harapan Bunda Wita, an inclusive school located in Kartasura, Sukoharjo, from September to October 2024. Primary data were collected through interviews with key stakeholders, including the Chief of the Foundation, the Headmaster, and three teachers designated as mover teachers. Data analysis followed six stages: (1) data preparation and processing, (2) data review, (3) data coding, (4) thematic description and setting, (5) presentation of results, and (6) interpretation of data and findings. Findings reveal that school management at Harapan Bunda Wita within the Sekolah Penggerak program is effectively carried out through the four core management functions: Planning, Organizing, Actuating, and Controlling (POAC). These functions were found to be well-integrated into the school's daily operations. Despite the effective implementation of POAC, several challenges were identified, particularly in three key areas. Nonetheless, appropriate and context-specific solutions have been applied to overcome these obstacles, ensuring that the management processes continue to support the program's goals. The study highlights the importance of strategic and adaptive management in inclusive early childhood education within government-initiated improvement frameworks.